A look into the state: Education in a Shipibo-Conibo community - Rolando, Giancarlo (2012)
The State makes itself present in its citizen’s everyday life by means of the interactions in which the latter engage with those public servers labeled as Street-level bureaucrats by Michael Lipsky, such as policemen or schoolteachers. This article deals with this kind of encounters in the context of a Shipibo-Conibo community. The State that partakes in the commoners’ everyday experience, through the actions (and omissions) of the school teachers stationed in the schools located in their community, shows discriminating and colonizing nature through its actions (and omissions). Furthermore, it does not satisfy its citizens’ expectations or help them accomplish their life-projects. Given this situation, commoners demand a better educational service and respect for their ethnic particularities.